Financial Performance and Risk - Rahmawan, Rizal; Bakar, Armi (Journal Research of Social Science, Economics, and Management, 2023)
When it comes to consumer-goods companies in particular, having shareholders who invest in the company’s stock is a major factor in the company’s success. In which the investors naturally demand return of their money. Where annual financial reports provide shareholders with a window into firm performance and allow them to steer its future direction. However, in the process of developing any organization, there are a number of dangers that must be dealt with quickly so as to not have a long-lasting unfavorable influence. This is why the effects of financial performance and risk on stock returns of consumer goods companies listed on the Indonesia Stock Exchange for the period 2016-2021 is of interest to scholars. The research aims to answer the question, "Does financial performance and risk affect the stock returns of companies listed on the IDX?" over the time period of 2016-2021, with a focus on the consumer products industry. Methodologically, this study employs descriptive quantitative methodologies for data collecting by way of audited financial accounts. Purposeful sampling was used to choose 50 participants. SPSS 17 was used to do the statistical analysis on the gathered data with the results that CR, DER, ROA, and risk have an influence on stock returns even though the levels of influence are different. Current ratio and DER have a negative and insignificant effect. While ROA and Risk have a positive and significant influence. While the effect value is 89.3%.